Knjiga povzetkov / Peti slovenski entomološki simpozij z mednarodno udeležbo, posvečen 80-letnici akademika prof. dr. Matije Gogala in 50-letnici smrti prof. dr. Štefana Michielija, Maribor, 21. in 22. september 2018: Book of Abstracts / Fifth Slovenian Entomological Symposium with International Attendance, dedicated to academician prof. dr. Matija Gogala on the occasion of his 80th birthday and 50th anniversary of the death of prof. dr. Štefan Michieli, [Maribor], 21st and 22nd September 201 (University of Maribor Press, 2018)
The Fifth Slovenian Entomological Symposium, with International Attendance, was dedicated to the Academician Professor Matija Gogala on the occasion of his 80th birthday and to the 50th anniversary of the death of Prof. Dr. Štefan Michieli. The Symposium was attended by 50 participants. Scientists from ten countries (Austria, Bosnia and Herzegovina, Croatia, France, Kosovo, Hungary, Macedonia, Slovenia, Russia and the United Kingdom) presented their work. The official languages of the Symposium were Slovenian and English. Authors explored a range of insect groups: Plecoptera, Odonata, Orthoptera, Hemiptera, Megaloptera, Neuroptera, Coleoptera, Hymenoptera, Diptera and Lepidoptera. Topics were presented in the fields of physiology, ethology, systematics and evolution, faunistics, ecology, applied entomology, nature conservation and history of entomology.